The Concept of Nature According to Syed M Naquib Al-AttÄs: The Perspective of New Kalam - Kholili Hasib; Zainal Abidin (Potret Pemikiran, 2023)
This article explains the views of Syed M Naquib al-Attas on the concept of nature from the perspective of the issue of kalam jadid. The study from the perspective of kalam jadid is important in this modern era because the issue of kalam jadid challenges religious thought to be able to answer actual issues around modernity with rational arguments. Kalam jadid is a kalam developed from classical issues based on the dirasatul firaq. Therefore, the study of kalam jadid is not limited to the problem of firqah thought (limited to the debate on the nature of qadm or hadith, but based on the development of modern science in the perspective of Islamic worldview. This article uses a descriptive method with a philosophical approach. Data were obtained by surveying the relevant literature and discussion. The data is then analyzed by means of discourse analysis which enables the researcher to uncover hidden intentions in the text. The results of this study concludes that al-AttÄs's thoughts on the concept of nature can be categorized as the issue of kalam jadd. The al-AttÄs method of describing the concept of nature based on the Islamic worldview can be a model in studying and developing the science of kalam in the modern era. This is the basis for the rise of new kalam (new kalam/JadÄ«d kalam). The study of kalam involves a variety of sciences: sufism, metaphysics, philosophy, and science. Thus, the science of kalam becomes a science that is more meaningful in various fields of science.